Penerapan Metode Extreme Programming dalam Pengembangan Aplikasi Point of Sale pada Usaha Phi Phi Thai - Anggara S (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2025)
In the current digital era, managing sales transactions manually is inefficient and prone to recording errors. This research aims to develop a web-based Point of Sale (POS) application for the Phi Phi Thai business using the Extreme Programming (XP) software development methodology. XP was chosen for its support of rapid iteration, adaptability to changing user requirements, and strong collaboration between developers and stakeholders. The developed application includes key features such as user registration and login, product ordering, menu and customer management, expense tracking, and financial and sales reporting. Testing was conducted using the Black Box Testing method to ensure that all functionalities performed according to specifications. The implementation results indicate that the application improves operational efficiency, reduces transaction errors, and provides real-time information for business owners to support better decision-making. Furthermore, the application of Extreme Programming (XP) methodology in the development process allows time for regular evaluation and refinement of the application based on feedback from end users. Each iteration produces a version of the software that can be immediately tested and used, minimizing the risk of system failure during final implementation. This approach also encourages lightweight yet relevant documentation and open communication between the technical team and business owners. Thus, the developed Point of Sale application not only meets current functional requirements but also has a high degree of flexibility for further development as Phi Phi Thai's business grows in the future.